Legal Certainty of Fulfilment of Registered Trademark Rights Owned by the Company for the Similarity of Trademarks in Principal - Anugrah Syahrial; Alfalah Naufal Yufianda; Hafiyyan Daffa Muhammad; Giovanni Akmal Firdausy (Journal of Law, Politic and Humanities, 2025)
The main function of a brand is to differentiate a company's products. A brand can create a reputation regarding quality, quantity and distinctiveness that is only owned by the party attached to the brand rights which are exclusively owned by the brand holder. However, it cannot be denied that later it was discovered that there were two brands that were fundamentally similar, causing disputes. The aim of this research is to explore the legal certainty of fulfilling a company's registered trademark rights for the existence of substantially similar brands by examining the concept of the element of "substantial similarity" in brands and efforts to overcome the existence of essentially similar brands. The research method used is normative juridical, with a statutory, legal conceptual and case approach. Data comes from secondary data, including primary legal materials, secondary legal materials and tertiary legal materials. Data analysis is descriptive analytical. The results of the research found that the concept of the element of "substantial similarity" in a brand has been regulated in statutory regulations, which shows that legal certainty has been sought. Efforts to overcome legal enforcement of trademark disputes based on similarities in essence which actually injure the actual rights of brand owners can be realized by standardizing law enforcement procedures, strengthening laws and regulations, supervision and outreach. Efforts to overcome this require synergy between the government, law enforcement, brand owners, and even the general public.